2010
DOI: 10.1021/jf100111e
|View full text |Cite
|
Sign up to set email alerts
|

Trypsin from the Processing Waste of the Lane Snapper (Lutjanus synagris) and Its Compatibility with Oxidants, Surfactants and Commercial Detergents

Abstract: A trypsin from the viscera of the lane snapper (Lutjanus synagris) was purified by heat treatment, fractionation with ammonium sulfate and affinity chromatography. The molecular weight of the enzyme was estimated to be 28.4 kDa (SDS-PAGE). The purified enzyme was capable of hydrolyzing the specific substrate for trypsin benzoyl-arginine-p-nitroanilide (BApNA) and was inhibited by benzamidine and tosyl lysine chloromethyl ketone (TLCK), synthetic trypsin inhibitors and phenylmethylsulfonyl fluoride (PMSF), whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 36 publications
(88 reference statements)
3
10
0
Order By: Relevance
“…The loss of enzymatic activity at pH values outside the range is probably caused by protein conformational changes as a result of charge repulsion [23]. Similar behavior was observed for trypsin from Nile tilapia [1], pirarucu [2], silver mojarra [3], lane snapper [4], Monterey sardine [9], sardine [10], jacopever and elkhorn sculpin [11], skipjack tuna [12], brownstripe red snapper [13], and grey triggerfish [24] and crude extract from crevalle jack [16]. According to Maurer [25], the optimum pH is a relevant parameter that indicates the potential utilization of enzymes in detergent formulations to be used in the alkaline pH range.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…The loss of enzymatic activity at pH values outside the range is probably caused by protein conformational changes as a result of charge repulsion [23]. Similar behavior was observed for trypsin from Nile tilapia [1], pirarucu [2], silver mojarra [3], lane snapper [4], Monterey sardine [9], sardine [10], jacopever and elkhorn sculpin [11], skipjack tuna [12], brownstripe red snapper [13], and grey triggerfish [24] and crude extract from crevalle jack [16]. According to Maurer [25], the optimum pH is a relevant parameter that indicates the potential utilization of enzymes in detergent formulations to be used in the alkaline pH range.…”
Section: Resultsmentioning
confidence: 80%
“…Fish trypsins have molecular masses between 23 and 28 kDa, e.g., Oreochromis niloticus (23.5 kDa) [1], Colossoma macropomum (23.9 kDa) [5], Gadus macrocephalus (24 kDa) [19], Pseudupeneus maculatus (24.5 kDa) [6], Sardina pilchardus (25 kDa) [10], Diapterus rhombeus (26.5 kDa) [3], Salaria basilisca (27 kDa) [20], Pterygoplichthys disjunctivus (27.5 kDa) [21], Arapaima gigas (28 kDa) [2], Pomatomus saltatrix (28 kDa) [22], and Lutjanus synagris (28.4 kDa) [4]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Usefulness of alkaline proteases in the facilitation of blood stains removal from cotton cloth was reported (37,38). The addition of proteases to detergents considerably increases the cleaning effect by removing protein stains and the consumption of surface active substances, thereby decreasing the pollution load (39).…”
Section: Removing Of Blood Stainmentioning
confidence: 99%
“…On the other hand, Kubota et al reported that high concentrations of Triton X-100 (1-10%) did not effect, or had a negligible effect, on the activity of two carboxypeptidases isolated from the exocarp of mandarin oranges (27). At the same time, it has been shown that the activities of trypsin from Bacillus licheniformis and trypsin isolated from fish intestine (lane snapper) were inhibited by 20 and 14%, respectively, in the presence of this surfactant (28,29). Pancreatin, however, is a multicomponent enzyme mixture, and we cannot say what the influence of this surfactant on the individual enzymes is.…”
Section: Effect Of Non-ionic Surfactants On Pancreatin Proteolytic Acmentioning
confidence: 96%